2019
DOI: 10.1016/j.bpj.2018.11.1166
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of DNA Target Searching and Cleavage by CRISPR-Cas12a

Abstract: Cas12a (also called Cpf1) is a representative type V-A CRISPR effector RNAguided DNA endonuclease, which provides an alternative to type II CRISPR-Cas9 for genome editing. Previous studies have revealed that Cas12a has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(62 citation statements)
references
References 0 publications
13
49
0
Order By: Relevance
“…This model ( Fig. 1 and SI Appendix) is based on recent structural biology and single-molecule studies (38,39) which revealed that DNA hydrolysis by Cas12a occurs in three discrete stages: "PAM attachment," where Cas12a latches onto a PAM site; "crRNA-DNA inspection," where Cas12a forms a partial crRNA-DNA hybrid; and "reconfiguration," where the protein forms a ternary complex and undergoes a conformal change that exposes its catalytic residues. While the final DNA cleaving step occurs after approximately 1 min under the conditions tested in ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model ( Fig. 1 and SI Appendix) is based on recent structural biology and single-molecule studies (38,39) which revealed that DNA hydrolysis by Cas12a occurs in three discrete stages: "PAM attachment," where Cas12a latches onto a PAM site; "crRNA-DNA inspection," where Cas12a forms a partial crRNA-DNA hybrid; and "reconfiguration," where the protein forms a ternary complex and undergoes a conformal change that exposes its catalytic residues. While the final DNA cleaving step occurs after approximately 1 min under the conditions tested in ref.…”
Section: Resultsmentioning
confidence: 99%
“…While the final DNA cleaving step occurs after approximately 1 min under the conditions tested in ref. 38, Cas12a molecules with inactivated nuclease sites remain stably bound to their DNA target for more than 500 s. Hence, the reconfiguration step effectively has no detectable off rate, suggesting that DNA cleavage may be inevitable (given enough time) after Cas12a has reached this stably bound ternary state. The same stability has also been observed in single-molecule Cas9 experiments (37).…”
Section: Resultsmentioning
confidence: 99%
“…The process by which the CRISPR effectors find their target has also received a lot of (35,37,87,88). For both, there is a first step of 3D-diffusion until a DNA molecule is encountered (35).…”
Section: Switching Crispr On and Off: A Matter Of Timingmentioning
confidence: 99%
“…On the other hand, the ampli ed products generated during the RPA continuously trigger CRISPR-Cas12abased collateral cleavage activity. Previous studies 14,17 have demonstrated that the collateral cleavage activity of the CRISPR-Cas12a system is independent of target strand cleavage. Therefore, target sequences for our AIOD-CRISPR assay are not limited by the Cas12a's protospacer adjacent motif (PAM) 22 .…”
Section: Resultsmentioning
confidence: 99%
“…and Cas13a, perform strong collateral cleavage activities in which the Cas nucleases activated by crRNAtarget duplex can indiscriminately cleave surrounding non-target single-stranded nucleic acids. 13,14,15,16,17 By combining with RPA pre-ampli cation, Cas13 and Cas12a nucleases have, respectively, been used to develop SHERLOCK (Speci c High-sensitivity Enzymatic Reporter UnLOCKing) system 18 and DETECTR (DNA Endonuclease-Targeted CRISPR Trans Reporter) system 14 for highly sensitive and speci c nucleic acid detection. Apart from the RPA pre-ampli cation method, some CRISPR-Cas-based nucleic acid detection utilized LAMP and PCR pre-ampli cation, such as CRISPR-Cas12b-assisted HOLMESv2 platform and SARS-CoV-2 DNA Endonuclease-Targeted CRISPR Trans Reporter (DETECTR).…”
Section: Introductionmentioning
confidence: 99%